Assessing the suitability of information technology in supporting knowledge sharing in islamic banks in Malaysia - Abuazoum, Abdusalam A.A.; Ahmad, Nursilah; Nurdiana Azizan (Asian Research Publishing Network, 2024)
Indexed by Scopus